Tahlīl al-kalāmi al-Insyāi al-Ṭalabī fī Surah Ghāfir wa Ma’ānihi (Dirāsah ‘IlmI al-Ma’ānī) - Saputra, Ferry (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research examines the analysis of ma'na in kalam insha'i thalaby in surah ghafir. The aim of this is to describe and find out the meaning contained in surah ghafir from the perspective of kalam isyai thalabi. There are several Kalam insyai thalabi found in Surah Ghafir, namely: 1. There are 22 forms of Al-'Amr found. 2. Al-Nahyu was found in 10 forms, 3. Al-Istifham was found in 5 forms, 4. Al-Tamanni was found in 2 forms, and 5. Al-Nida was found in 5 forms. Meanwhile, the method used in this research is descriptive qualitative in Surah Ghafir which describes the data obtained from Surah Ghafir in Kalam Insha’i Thalabi.